Stock market liquidity and firm performance: Evidence from a Frontier Market - Fernando, W.M.D.N.; Samarakoon, S.M.R.K. (University of Jaffna, 2020)
This paper examined the relationship of stock market liquidity on Sri Lankan Non Financial firms' performance incorporated in the Colombo Stock Exchange (CSE) from 2015 to 2019. The ordinary least squares regression model was used to evaluate the relationship. Empirical findings endorse the stock market liquidity consequences of firm performance: stronger stock liquidity results in the firm’s higher performance. The empirical findings showed a positive relationship between stock market liquidity as measured by the Amivest measure and the firm output as measured by Tobin's Q.
Keywords: Amivest measure; Colombo Stock Exchange; firm performance; stock market liquidity; Tobin’s q